You'd be home now - Glasgow, Kathleen, 1969- (Delacorte Press, 2021)
After a fatal car accident that reveals Emory's brother Joey's opioid addiction, Emory struggles to help him on his road to recovery and make herself heard in a town that insists on not listening.